Upaya Peningkatan Hasil Belajar PAK dengan Metode PBL Berbantuan Youtube Di SMA Xaverius 1 Palembang - Lestari Febrianti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Religion plays a very important role in human life, so it is necessary to have religious education in order to become a human being who has faith and devotion to God Almighty, has noble character and develops spiritual potential. School is the second place where students develop in their faith through Catholic religious education lessons. However, at SMA Xaverius 1 Palembang they are less interested in participating in PAK lessons, because they are more concerned with other subjects and view PAK lessons as unimportant lessons. For those who are important, complete grades are important, so that they do not understand the content of the material presented. In this research, learning is offered using the problem based learning method assisted by YouTube. Where in learning groups are formed and problems/cases that exist in society are presented. Students are invited to reason critically in solving existing problems. The aim is to create a sense of interest in learning, achieve satisfactory learning outcomes, increase awareness of what occurs in the surrounding environment and increase respect for human life, both oneself and others, in everyday life. This research was carried out as classroom action research, carried out at SMA Xaverius 1 Palembang in class XII IPS 3 on the material